PENGGUNAAN MEDIA PEMBELAJARAN OLEH PENDIDIK PAK SEMESTER GENAP TA 2016-2017 DI STT KRISTUS ALFA OMEGA SEMARANG - Yulia, Tantri (Sekolah Tinggi Teologi Kristus Alfa Omega, 2017)
The use of instructional media is related to the suitability of various things, among others: learning objectives, learning materials, characteristics of learners, learning theories, learning styles of learners, environmental conditions, support facilities, time available, cost, organizational support, participant learning style educate and environmental conditions. Compatibility with other things also supports the effective use of media, but has not been discussed in this study. Educators in the